Comparative thermal characteristics and fatty acid composition of mono- and Diacylglycerols of lard and some commercial emulsifiers - Nasyrah, A.R.; Marikkar, Mohammed Nazrim; Dzulkifly, M.H. (Taylor and Francis, 2014)
A study was carried out to compare the fatty acid composition and thermal profiles of mono- (MAG) and di-acylglycerols (DAG) of six commercial emulsifiers coded as E1, E2, E3, E4, E5 and E6 purchased from different manufacturers with those of the same derived from lard (LD). The lipid extraction from the commercial emulsifiers was done using soxhlet method and the isolation of individual MAG and DAG was carried out using column chromatographic method. The isolated partial acylglycerols of LD and individual emulsifiers were subjected to fatty acid analysis by gas chromatography and thermal analysis by differential scanning calorimetry. A clear distinction between LD based emulsifier and the commercial emulsifies was achieved by the application of principal components analysis (PCA) to the fatty acid data. According to thermal analysis, MAG and DAG of LD displayed significant differences from those of commercial MAG and DAG with respect to the thermal transitions in the cooling curves. This study concluded that partial acylglycerols of none of the commercial emulsifiers employed in this study displayed similarity to those of LD based emulsifiers.